GEODIVERSIDAD, ORDENAMIENTO TERRITORIAL Y ÁREAS NATURALES PROTEGIDAS - Corona, Alberto Pereira; Servón, Patricia Fragoso; Martínez, Salvador Adame; Granados, Alejandro R. Alvarado; Verges, Fernando A. Rosete (European Scientific Journal, ESJ, 2015)
The evaluation of the legal instruments for planning and management of natural resources as well as for its preservation or protection in light of new approaches and knowledge is a need to maintain the validity of these instruments. Evaluation results of the Territorial Ecological Ordinances (OET) and the decrees of Protected Natural Areas (ANP) in Quintana Roo, Mexico from the point of view of spatial congruence of them to protect the Geodiversity and Biodiversity in the State are presented. Semiquantitative values of geodiversity for Quintana Roo are reported and those legal instruments are compared in terms of the acreage with higher values of geodiversity found in areas established for protection or conservation in those instruments. Some arguments, based on the results of the spatial analysis are provided to support the complementarity of the instruments in the management of territory and resources. The methodology permitted to identify some inconsistencies in the zoning of OETs.